A method for quantifying limbal stem cell niches using OCT imaging. Issue 9 (22nd February 2017) - Haagdorens, Michel; Behaegel, Joséphine; Rozema, Jos; Van Gerwen, Veerle; Michiels, Sofie; Ní Dhubhghaill, Sorcha; Tassignon, Marie-José; Zakaria, Nadia
Abstract : Aims: To evaluate the efficacy of Fourier domain-optical coherence tomography (FD-OCT) in imaging and quantifying the limbal palisades of Vogt and to correlate these images with histological findings. Methods: The superior and inferior limbal region of both eyes of 50 healthy volunteers were imaged by FD-OCT. Images were processed and analysed using Matlab software. In vitro immunofluorescent staining of a cadaveric donor limbus was analysed to correlate the presence of stem cells in the visualised structures. Results: FD-OCT could successfully visualise limbal crypts and the palisades of Vogt in the limbus region. Fluorescent labelling confirmed the presence of stem cells in these structures. The mean palisade ridge width (ΔPR ) and the mean interpalisade epithelial rete peg width (ΔERP ) were both of the order of 72 μm, leading to a palisade density (PD) of about 7.4 palisades/mm . A significant difference in ΔPR, ΔERP and PD was seen between the inferior and superior sides of the right eye and the superior sides of the left and right eye(p<0.05.). A significant influence of iris colour on parameters ΔPR, ΔERP and PD was found, and of age on PD and ΔERP (p<0.05). Conclusions: In vivo OCT imaging is a safe and effective modality to image the limbus and can be used to visualise the palisades of Vogt. Image processing using Matlab software enabled quantification and density calculation of imaged limbal palisades of Vogt. This technique may enhance targeted limbal biopsies for transplantation.